Evolution of the macromolecular structure of sporopollenin during thermal degradation. Issue 2 (October 2015) - Bernard, S.; Benzerara, K.; Beyssac, O.; Balan, E.; Brown Jr., G.E.
Abstract: Reconstructing the original biogeochemistry of organic microfossils requires quantifying the extent of the chemical transformations they experienced during burial and maturation processes. In the present study, fossilization experiments have been performed using modern sporopollenin chosen as an analogue for the resistant biocompounds possibly constituting the wall of many organic microfossils. Sporopollenin powder has been processed thermally under argon atmosphere at different temperatures (up to 1000 °C) for varying durations (up to 900 min). Solid residues of each experiment have been characterized using infrared, Raman and synchrotron-based XANES spectroscopies. Results indicate that significant defunctionalisation and aromatization affect the molecular structure of sporopollenin with increasing temperature. Two distinct stages of evolution with temperature are observed: in a first stage, sporopollenin experiences dehydrogenation and deoxygenation simultaneously (below 500 °C); in a second stage (above 500 °C) an increasing concentration in aromatic groups and a lateral growth of aromatic layers are observed. With increasing heating duration (up to 900 min) at a constant temperature (360 °C), oxygen is progressively lost and conjugated carbon–carbon chains or domains grow progressively, following a log-linear kinetic behavior. Based on the comparison with natural spores fossilized within metasediments which experienced intense metamorphism, we show that the present experimental simulations may not perfectly mimic natural diagenesis and metamorphism. Yet, performing such laboratory experiments provides key insights on the processes transforming biogenic molecules into molecular fossils.